2022
DOI: 10.1101/2022.03.04.22271706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remdesivir for the treatment of patients hospitalized with COVID-19 receiving supplemental oxygen: a targeted literature review and meta-analysis

Abstract: This network meta-analysis (NMA) assessed the efficacy of remdesivir in hospitalized patients with COVID-19 requiring supplemental oxygen. Randomized controlled trials of hospitalized patients with COVID-19, where patients were receiving supplemental oxygen at baseline and at least one arm received treatment with remdesivir, were identified. Outcomes included mortality, recovery, and no longer requiring supplemental oxygen. NMAs were performed for low-flow oxygen (LFO2); high-flow oxygen (HFO2), including NIV;… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(86 reference statements)
1
2
0
Order By: Relevance
“…Although the RDV-treated group was characterized by a lower percentage of patients requiring mechanical ventilation during both pandemic waves, the difference with a group not receiving any antiviral therapy was statistically insignificant. Nevertheless, the demonstration of a favorable trend in this regard is in line with reports by other authors 43,44 . Even the Solidarity trial, the initial results of which were the basis for not recommending RDV in the WHO guidelines, in the final report published in 2022 documented a significant beneficial effect on reducing mortality and disease progression requiring mechanical ventilation 45 .…”
Section: Discussionsupporting
confidence: 93%
“…Although the RDV-treated group was characterized by a lower percentage of patients requiring mechanical ventilation during both pandemic waves, the difference with a group not receiving any antiviral therapy was statistically insignificant. Nevertheless, the demonstration of a favorable trend in this regard is in line with reports by other authors 43,44 . Even the Solidarity trial, the initial results of which were the basis for not recommending RDV in the WHO guidelines, in the final report published in 2022 documented a significant beneficial effect on reducing mortality and disease progression requiring mechanical ventilation 45 .…”
Section: Discussionsupporting
confidence: 93%
“…Based on obtained results, Remdesivir did not any significant difference in mortality rate in hospitalized adults with COVID-19; however, it can improve the percent recovered, decreases serious injuries, and probably leads to a decline in the rate of mechanical ventilation [ 19 – 21 ]. The National Institutes of Health guidelines later recommended that combining Remdesivir with anti-inflammatory drugs such as Tocilizumab, corticosteroids, and Baricitinib, can increase the benefit observed across all endpoints in patients with pneumonia and on oxygen support [ 22 24 ]. Recently have been indicated that early Remdesivir therapy in patients with active malignancies reduces 28-day in-hospital mortality by 80% [ 25 ].…”
Section: Therapeutic Agentsmentioning
confidence: 99%
“…The network meta-analysis involving six studies was performed to assess the efficacy of remdesivir in hospitalized patients with COVID-19 requiring supplemental oxygen. Among patients requiring supplemental oxygen at baseline, the use of remdesivir compared to best supportive care improved the risk of mortality, recovery, and need for oxygen support in patients receiving oxygen at any flow or low flow [18].…”
mentioning
confidence: 99%